2005
DOI: 10.1097/01.ju.0000154631.92150.ef
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Resiniferatoxin for the Treatment of Interstitial Cystitis: A Randomized, Double-Blind, Placebo Controlled Trial

Abstract: In the largest prospective, randomized clinical trial reported to date with intravesical vanilloid therapy, single administration of RTX at doses of 0.01 microM to 0.10 microM was not effective in patients with interstitial cystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(110 citation statements)
references
References 16 publications
5
104
0
1
Order By: Relevance
“…Of the trials included, 4 reported BCG compared with placebo [32][33][34][35], 3 evaluated BoNTA in comparison with placebo [8,36,37], 2 reported RTX compared with placebo [38,39], 2 comparatively assessed chondroitin sulfate and placebo [7,40], 2 reported PPS compared with placebo [5,41], 1 evaluated lidocaine compared with placebo [42], 1 reported oxybutynin compared with placebo [43], and 1 assessed BCG in comparison with BoNTA [44]. The studies included assessed 905 patients in all.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the trials included, 4 reported BCG compared with placebo [32][33][34][35], 3 evaluated BoNTA in comparison with placebo [8,36,37], 2 reported RTX compared with placebo [38,39], 2 comparatively assessed chondroitin sulfate and placebo [7,40], 2 reported PPS compared with placebo [5,41], 1 evaluated lidocaine compared with placebo [42], 1 reported oxybutynin compared with placebo [43], and 1 assessed BCG in comparison with BoNTA [44]. The studies included assessed 905 patients in all.…”
Section: Resultsmentioning
confidence: 99%
“…Female patients accounted for at least 77 % of all subjects, who were all 18 years or older, excluding one study that did not mention patient age [35]. One study had a three-arm design, and included 0.05 μM RTX, 0.1 μM RTX, and placebo control groups [38]; another study had a four-arm design, and included 0.01 μM RTX, 0.05 μM RTX, 0.1 μM RTX, and placebo control groups [39]. Five studies identified additional treatments in both groups, including hydrodistention [8,37], oral PPS [5,41], and antibiotics [45].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 95 patients who completed the doubleblind placebo-controlled phase, 82 (86%; 41 from each group) elected to receive open-label treatment with PSD597 for 5 days (days [15][16][17][18][19]. Of these 82 patients, most (64, 78%), had improved GRA scores at day 22 (3 days after the end of open-label treatment) than before treatment; 11 (13%) were unchanged and four (5%), all of whom had initially received placebo during the double-blind phase, had worse scores.…”
Section: Resultsmentioning
confidence: 99%
“…Heparin is one of the most widely used intravesical therapies, but when used alone, has not been shown to produce immediate and sustained relief of symptoms [13]. Intravesical hyaluronic acid, chondroitin sulphate, the neurotoxins capsaicin and resiniferatoxin, and BCG have also been used as intravesical agents, but so far RCTs have shown them to be of little value [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized, double-blind, placebo-controlled trial published in 2005, no statistically significant benefit was seen with the use of this agent. 50 On the basis of currently available evidence, both BCG and resiniferatoxin should still be considered investigational interventions for the management of IC symptoms.…”
Section: Bacillus Calmette-guèrin and Resiniferatoxinmentioning
confidence: 99%